High yield recovery of 2, 3-butanediol from fermented broth accumulated on xylose rich sugarcane bagasse hydrolysate using aqueous two-phase extraction system. (October 2021) - Narisetty, Vivek; Amraoui, Yassin; Abdullah, Alamri; Ahmad, Ejaz; Agrawal, Deepti; Parameswaran, Binod; Pandey, Ashok; Goel, Saurav; Kumar, Vinod
Graphical abstract: Highlights: BDO accumulated on xylose-rich sugarcane bagasse hydrolysate was purified. Maximum extraction was recorded with 30% w/v (NH4 )2 SO4 and 50% v/v isopropanol. BDO partition coefficient of 45.5 and recovery yield of 97.9% was achieved. Similar BDO recovery results were obtained with unfiltered fermented broth. Purified BDO was characterized through 13 C NMR and 1 H NMR spectroscopy. Abstract: Downstream processing of chemicals obtained from fermentative route is challenging and cost-determining factor of any bioprocess. 2, 3-Butanediol (BDO) is a promising chemical building block with myriad applications in the polymer, food, pharmaceuticals, and fuel sector. The current study focuses on the recovery and purification of BDO produced (68.2 g/L) from detoxified xylose-rich sugarcane bagasse hydrolysate by a mutant strain of Enterobacter ludwigii . Studies involving screening and optimization of aqueous-two phase system (ATPS) revealed that 30% w/v (NH4 )2 SO4 addition to clarified fermented broth facilitated BDO extraction in isopropanol (0.5 v/v), with maximum recovery and partition coefficient being 97.9 ± 4.6% and 45.5 ± 3.5, respectively. The optimized protocol was repeated with unfiltered broth containing 68.2 g/L BDO, cell biomass, and unspent protein, which led to the partitioning of 66.7 g/L BDO, 2.0 g/L xylose and 9.0 g/L acetic acid into organic phase with similar BDO recovery (97%) and partition coefficient (45).